Electromagnetic Interference with the On-board Balise Transmission Module Antennas of Urban Rail Transit Train - ZHANG Dong; YI Yongqiang; GUO Ningbo; ZHAO Teng (Chengshi guidao jiaotong yanjiu)
［Objective］ The electromagnetic environment of urban rail transit train is relatively complex. The on-board BTM (balise transmission module) antenna is highly susceptible to electromagnetic interference, which may easily lead to potential safety hazards during train operation. Therefore, it is necessary to conduct research on the electromagnetic interference with the on-board BTM antenna. ［Method］ The electromagnetic interference with the on-board BTM antenna that occurred on Qingdao Metro Line 8 is taken as an example, the main causes of the electromagnetic interference are investigated from the basic elements such as sensitive equipment, interference sources and interference paths. An optimization plan is formulated according to the actual situation on site and the investigation results, corresponding dynamic tests are carried out. ［Result & Conclusion］ Through investigation, it is concluded that the interference source originates from the three-phase inverter unit of the auxiliary inverter, and the interference path comes from the high-frequency current in the return cable. An optimization plan of adding a 0.5 μF capacitor to the negative input line of the auxiliary inverter is formulated, which can effectively reduce the impact of the train electromagnetic interference on the BTM antennas and ensure the train normal operation.